Seleksi Bakteri Asam Laktat Pada Fermentasi Spontan Biji Kopi Robusta dan Karakterisasi Enzim - Ramadhani, Djihan; Patang, Patang; Putra, Reski Praja (Jurnal Pendidikan Teknologi Pertanian, 2024)
Lactic Acid Bacteria (LAB) are natural bacteria that play an important role in the fermentation process. These bacteria can produce cellulase and pectinase enzymes. This study aims to examine isolates of lactic acid bacteria involved in the spontaneous fermentation of amylolytic robusta coffee beans and to examine the effect of incubation time, pH and temperature on the activity of the amylase enzyme produced. This study used the experimental method with a completely randomized design (CRD). The stages in this study were the preparation of equipment and media, selection of amylolytic LAB, determination of the optimum incubation time, and characterization of the amylase enzyme. The results showed that there were 2 isolates capable of producing clear zones, namely isolates BT2411 and BT2412. The clear zone indicates the presence of amylolytic LAB in the tested isolates. BT24I1 isolate is a LAB isolate which produced the highest clear zone with a diameter of 2.43 mm. Testing the incubation time showed that isolate BT24I1 produced the optimum amylase enzyme at 48 hours of incubation with a specific amylase activity value of 0.64 U/ml. The characteristics of the amylase enzyme produced by BAL BT24I1 isolate are optimum at pH 4.5 with enzyme activity of 19.89 U/ml and optimum at 45℃ with enzyme activity of 19.79 U/ml